FAKTOR-FAKTOR YANG MELATARBELAKANGI MOTIVASI SESEORANG UNTUK MENGGUNAKAN SUNTIKAN SILICONE CAIR DI MALANG TAHUN 2001 - Asmika, Asmika; Chuluq, Chusnul; Sutrisnani, Catur Suci (Fakultas Kedokteran Universitas Brawijaya, 2005)
ABSTRACT Recently it has been reported that some women have suffered from illness complication as the effect of the use the liquid silicone to beautify themselves. Knowledge deprivation and eagerness to achieve complete beauty in an easy and cheap way makes them undertake a short cut which is getting the injection. The research is intended to know some factors underlying a person’s motivation to use liquid silicone injection in Malang in 2001. The research was a descriptive cross sectional method. The population was person who use liquid silicone injection in Malang 2001, this assume were 20 persons during the research (June – December 2001). This research showed that 15 respondents (75 %) of the samples knew the benefits of liquid silicone injection but did not know the effect of the injection, the education of this respondents were secondary and tertiary level 13 respondents (65 %), 6 respondents (30 %) of the sample working as beauticians, 6 respondents (30 %) of the samples having salary Rp. 250.000,00 - Rp.500.000,00 per month, 9 respondents (45 %) of the samples feeling more beautiful and self confident after getting liquid silicone injection, 6 respondents (30 %) of the samples getting family permission, 12 respondents (60 %) of the samples having a social network to use the injection, 5 respondents (25 %) of the samples getting secondary health services and 4 respondents (20 %) of the samples getting